2020
DOI: 10.3389/fped.2020.00347
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Artery Banding for Ventricular Rehabilitation in Infants With Dilated Cardiomyopathy: Early Results in a Single-Center Experience

Abstract: Background: Pulmonary artery banding (PAB) is reported as an innovative strategy for children with end-stage heart failure (ESHF) to bridge to transplantation or recovery. We report our early experience with PAB to evaluate outcomes, indications, and limitations. Materials and Methods: This is a single-center prospective clinical study, including infants and children admitted for ESHF owing to dilated cardiomyopathy (DCM) with preserved right ventricular function after failure of maximal conventional therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…All but one (the most recent) underwent an elective percutaneous procedure for PAB balloon dilatation, after a median of 11 (7‐15) months from surgery, due to progressive RV hypertension and increased (≥moderate) tricuspid regurgitation. Procedures were well tolerated and patients gradually recovered from LV dysfunction, allowing delisting from HT in three cases, without recurrence of heart failure at last follow‐up, as we described elsewhere 31 …”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…All but one (the most recent) underwent an elective percutaneous procedure for PAB balloon dilatation, after a median of 11 (7‐15) months from surgery, due to progressive RV hypertension and increased (≥moderate) tricuspid regurgitation. Procedures were well tolerated and patients gradually recovered from LV dysfunction, allowing delisting from HT in three cases, without recurrence of heart failure at last follow‐up, as we described elsewhere 31 …”
Section: Resultsmentioning
confidence: 88%
“…Procedures were well tolerated and patients gradually recovered from LV dysfunction, allowing delisting from HT in three cases, without recurrence of heart failure at last follow-up, as we described elsewhere. 31 Analyzing the outcomes of this group, despite freedom from HT was 66.6% at last follow-up, because PAB strategy failed in two cases, requiring VAD support, survival was not affected since it was 100% at 1-year follow-up and 5-year follow-up (Figure 5). Noticeably, those patients who lastly required HT were the first patients of our experience.…”
Section: Pab Strategymentioning
confidence: 94%
See 2 more Smart Citations
“…It has been shown that there is myocyte regeneration after unloading of the dilated LV by mechanical circulatory support in pediatric dilated cardiomyopathy patients with end-stage HF [ 76 ]. The regenerative strategy is the basis of reversible pulmonary artery band (PAB) in infants and young children with dilated cardiomyopathy [ 77 , 78 ]. Application of a reversible PAB for 2–3 months can increase the contractility of LV by ventricle–ventricle interaction as both RV and LV share a common septum.…”
Section: Innovative Therapies For Acute and Chronic Hfmentioning
confidence: 99%